Visitors' behavioural intention towards an episode of air pollution: a segmentation analysis. Issue 6 (24th July 2021) - Carneiro, Maria João; Eusébio, Celeste; Rodrigues, Vitor; Robaina, Margarita; Madaleno, Mara; Gama, Carla; Monteiro, Alexandra
ABSTRACT: Despite the growing influence of air pollution on people's behaviour, little attention has been given to visitors' behavioural intentions towards air pollution episodes. Understanding visitors' behaviours is crucial in developing effective marketing strategies and preventing damaging consequences for both visitors and destinations. This paper presents a segmentation analysis based on visitors' behavioural intentions towards a hypothetical episode of air pollution, based on a visitor survey (N = 625) applied over the Central Region of Portugal. Two clusters with different behavioural intentions were obtained. Differences were found between groups regarding attitudes towards the environment, risk perceptions, travel behaviour and sociodemographic profile.